This quadratic equation which will have two solutions can be solved by completing the square or by using the quadratic equation formula.Completing the square:x2+18x+4 = 0(x+9)2+4 = 0(x+9)2+4-81 = 0(x+9)2 = 77x+9 = + or - the square root of 77x = -9 + or - the square root of 77If you're not too sure about the procedure of completing the square your maths tutor should be familiar with it.
x2-18x+81 = (x-9)(x-9) when factored
81. To complete the square of x^2 + 18x, you take half the coefficient of the x term (half of 18 is 9), and square that number (9 squared is 81). To confirm this works, you can now factor x^2 + 18x + 81 and see that it factors as (x+9)(x+9), or (x+9)^2, a perfect square.
18x2 +12x + 2 this is not a perfect square trinomial so let's work a little bit here. 18x2 +12x + 2 factor 2 = 2(9x2 +6x + 1) = 2(3x + 1)2 represent 2 as (√2)2 = (√2)2(3x + 1)2 = [(√2)(3x + 1)]2 take its square root = (√2)(3x + 1) for all x > -1/3.
Factors are: 9(x - 1)(x - 1) or (3x - 3)2, so yes, it is.
-26
That doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: (-1 plus or minus one third itimes the square root of 7) divided by 4.x = -0.25 + 0.22047927592204922ix = -0.25 - 0.22047927592204922iwhere i is the square root of negative one.
Yes.
This quadratic equation which will have two solutions can be solved by completing the square or by using the quadratic equation formula.Completing the square:x2+18x+4 = 0(x+9)2+4 = 0(x+9)2+4-81 = 0(x+9)2 = 77x+9 = + or - the square root of 77x = -9 + or - the square root of 77If you're not too sure about the procedure of completing the square your maths tutor should be familiar with it.
x2-18x+81 = (x-9)(x-9) when factored
81. To complete the square, halve the coefficient of the x term (18/2 = 9) and add the square of this (92 = 81) to both sides: x2 + 18x = -13 ⇒ x2 + 18x + 81 = -13 + 81 ⇒ (x + 9)2 = 68
81. To complete the square of x^2 + 18x, you take half the coefficient of the x term (half of 18 is 9), and square that number (9 squared is 81). To confirm this works, you can now factor x^2 + 18x + 81 and see that it factors as (x+9)(x+9), or (x+9)^2, a perfect square.
(x+9)^2 =x^2 + 9 X^2 + 18x + 81 = X^2 +9 18X + 72 = 0 18X = -72 X =- 4
If: x^2 +18x = 29 Then completing the square: (x+9)^2 -81 = 29 or (x+9)^2 = 110
18 feet x 20 feet = 360 square feet. There are 9 square feet in one square yard, so 360 square feet = 40 square yards, not 12 square yards.
false
No 9xx-18x+36 9(xx-2x+4) xx-2x+4 (doesn't factor evenly)